Teacher-student collaborative assessment (TSCA) in integrated language classrooms - Shuguang, Sun; Qiufang, Wen (Universitas Pendidikan Indonesia, 2018)
Assessing students’ productive performance is challenging in China because large class sizes inevitably lead to heavy workloads for teachers. To address this problem, a new method of assessment, teacher-student collaborative assessment (TSCA)—was proposed in 2016 to organize and balance different modes of teacher assessment, self-assessment, peer assessment, and computer-mediated assessment. The present study took one intact class as a case, aiming to explore how TSCA could be carried out efficiently and systematically in the classroom and how students perceived TSCA. Qualitative data obtained include students’ writing drafts and revision, interview, and reflective journals of the students and the teacher. Interview data indicated that the students responded to this type of assessment positively and thought they benefited greatly from the teacher’s instruction and peer discussion. This was triangulated by the students’ reflections in which all the students spoke highly of TSCA and agreed that this method was a good way to pinpoint their weaknesses and help them learn how to revise their essay better. The students reported that they formed a new perception of self-assessment and self-revision and felt that a lot was gained.